Internet GIS, Based on USLE Modeling, for Assessment of Soil Erosion in Songkhram Watershed, Northeastern of Thailand - Nontananandh, Supakij; Changnoi, Burin (Agriculture and Natural Resources, 2012)
A web-based geographic information system (GIS) was designed and implemented, which included a database designed to accommodate, organize and manipulate basic spatial data as well as interrelate data from various sources. The system was used to produce erosion susceptibility maps for regions of Upper Northeastern Thailand—an area that has suffered from inappropriate land use practice. GIS-based methods were proposed and applied to data from the Songkhram sub basin in the Songkhram watershed. ArcGIS software was used to derive land use, land cover and topographical data for the watershed. An open source GIS (QGIS) and the Geographic Resources Analysis Support System (GRASS) package were used to carry out geographical data analysis and database management system (DBMS) implementation, both of which were implemented by Postgres Plus software. The watershed was mapped into topographically and geographically homogeneous grid cells to capture watershed heterogeneity. The soil erosion in each cell was calculated using the universal soil loss equation by carefully determining its various parameters and classifying the watershed into different levels of soil erosion severity. The results showed that during the study period, the area had soil loss over a tolerance value (12.5 t.ha-1.yr-1) which ranged from the moderate class up to the very severe class of susceptibility. Moreover, it was also found that the amount of soil erosion increased from 762 km2 in 2006 and to 1,123 km2 in 2010. The outcome of the study was published on the Internet using UMN map server software as well as by using Google map.